Discoid Lupus Erythematosis affecting the Eyelid with Dramatic Response to Chloroquine and Intralesional Triamcinolone - Mahmood, Khalid (International Journal of Pathology, 2018)
Summary: The discoid lupus erythematosus (DLE) may present with a wide range of cutaneous lesions. However, the eyelidinvolvement has been only rarely reported. The involvement of eyelids may lead to potentially serious complicationssecondary to the scarring like ectropion, entropion, symblephron and loss of eyelashes. It is therefore important to diagnoseand appropriately treat the eyelid lesions of DLE at an early stage. A case of DLE involving the eyelid which respondeddramatically well to chloroquine and intralesional triamcinolone, is being reported.